Diagnostic score of cardiac involvement in AL amyloidosis. (10th July 2019) - Nicol, Martin; Baudet, Mathilde; Brun, Stephanie; Harel, Stephanie; Royer, Bruno; Vignon, Marguerite; Lairez, Olivier; Lavergne, David; Jaccard, Arnaud; Attias, David; Macron, Laurent; Gayat, Etienne; et al.
Abstract: Aims : Early diagnosis of cardiac involvement is a key issue in the management of AL amyloidosis. Our objective was to establish a diagnostic score of cardiac involvement in AL amyloidosis and to compare it with the current consensus criteria [i.e. left ventricular hypertrophy >12 mm and N-terminal pro b-type natriuretic peptide (NT-proBNP) >332 ng/L]. Methods and results : We carried out a prospective and multicenter study on AL amyloidosis patients who underwent cardiac evaluation including clinical examination, electrocardiography (ECG), cardiac biomarkers, transthoracic echocardiography (TTE), and cardiac magnetic resonance imaging (CMR). Cardiac involvement was based on CMR and/or endomyocardial biopsy. In a derivation cohort of 114 patients (82 with cardiac involvement), the highest diagnostic accuracy was observed with NT-proBNP and troponin blood levels, TTE-derived global longitudinal strain (LS), and apical to basal LS gradient. By using multivariate analysis, we established a diagnostic score including global LS ≥−17% (1 point), apical/(basal + median) LS ≥0.90 (1 point), and troponin T >35 ng/L (1 point). A score >1 was associated with sensitivity of 94% and specificity of 97%, an area under the curve of 0.98 [95% confidence interval (CI) 0.93–0.99] as well as a net reclassification index of 0.39 (95% CI 0.28–0.46) when compared with consensus criteria. In a validation cohort of 73 AL amyloidosis patients, the area under the receiver operating characteristic curve of the diagnostic score was 0.97 (95% CI 0.90–0.99). Conclusion : Combining T troponin blood levels and two echo-derived strain parameters leads to very high accuracy for diagnosing cardiac involvement in AL amyloid patients.